A career in statistics beyond the numbers - Hahn, Gerald J. (Wiley, 2011)
"This book serves as an excellent companion to its predecessor, The Role of Statistics in Business and Industry. In this volume, the authors help readers decide whether a career in statistics is appropriate for them and what to expect once in it. They provide insights into the work environment and how students and entry-level statisticians can best prepare themselves to succeed, offering hints for success in training, career paths, and lifelong learning. This book is a must-have for anyone considering a career in statistics, as well as for faculty who prepare students for such a career"--Provided by publisher.
Includes bibliographical references (pages 321-329) and index. - Print version record
Keywords: Statistics -- Vocational guidance; Statisticians -- Vocational guidance; Mathematical statistics; Commercial statistics; Statisticiens; Orientation professionnelle; Statistique; Orientation professionnelle; MATHEMATICS; Probability & Statistics; General; Statisticians; Vocational guidance; Statistics; Vocational guidance